Seeing the Big Picture Through Smaller Screens: Characterizing the Library Users' Experience on Mobile Devices. Issue 3 (2nd October 2017) - McCrillis, Aileen; Piazza, Allison; Larson, Catherine
ABSTRACT: Mobile devices are becoming profoundly important tools for finding and accessing information in medicine; however, accessing institution-licensed content on mobile devices can be problematic. An assessment was performed of selected library systems, publisher platforms, and licensed information resources for compatibility with several types of smartphones and tablets. The majority of products assessed had some form of mobile compatibility, but mobile compatibility varied among product categories and the form of mobile compatibility varied among products. This assessment reveals that users of academic health sciences libraries may have an incongruent user experience on mobile devices due to the diversity of digital platforms.